المستحقون للتنزيل في قانون الأسرة الجزائري على ضوء قرارات المحكمة العليا - دراسة مقارنة بالتشريعات العربية- - هلالي, مسعود (University of Eloued جامعة الوادي, 2021)
الدارس لقانون الأسرة الجزائري، يلحظ وجود العديد من المآخذ الشكلية منها والموضوعية التي تعتري نصوصه، لعل من أبرزها ما تعلق بأحكام" التنزيل" أو ما تطلق عليه التشريعات العربية المقارنة" الوصية الواجبة"، حيث كان هذا الموضوع - ولا يزال- محل اختلاف بين الدارسين لأحكامه، لاسيما فيما تعلق بمسألة أصحاب الحق في التنزيل أو الوصية الواجبة، الذي يرجع أساسا إلى تحديد مصطلح" الأحفاد"، إن على المستوى النظري؛ الصياغة التشريعية، أو التطبيقي؛ الأحكام والقرارات القضائية، إذ يجد الدارس لنصوص التنزيل في قانون الأسرة الجزائري( خاصة المادة 169)، اختلافا بَيِّنا بين القانونيين الذين عرضوا بالشرح لهذه المادة، حيث تخرج عن ذلك أقوال ثلاثة حول مدلول الأحفاد؛ المستحقين للتنزيل. بل تعدى الأمر إلى الجانب التطبيقي، حيث اختلفت القرارات القضائية الصادرة عن المحكمة العليا في هذا السياق. كما نجد التشريعات العربية المقارنة تعدّدت مواقفها من المسألة، بين مضيق وموسع. وليس أمر الاختلاف بشأن مدلول الأحفاد المستحقين للوصية الواجبة حصرا على التشريع والقضاء الجزائريين، بل الأمر كذلك في التشريعات العربية المقارنة، التي تعدّدت مواقفها من المسألة بين مضيق وموسع. A student of Algerian family law, notes the existence of many formal and objective gaps in his texts, the most striking of which are perhaps linked to the provisions of the "revelation" or to what comparative Arab legislation calls "The mandatory will " Where has this topic been - and still is - the subject of disagreement among scholars regarding its decisions, particularly with regard to the issue of right holders in inheritance by substitution Or the compulsory will, which is mainly due to the definition of the term "grandchildren", Or the compulsory will, which is mainly due to the definition of the term "grandchildren", It is at the theoretical level; Drafting of legislative or implementing texts; Judgments and judicial decisions, as the student finds texts of inheritance by substitution In Algerian family law (in particular article 169), There is an obvious difference between the legal scholars who explained this article, as there are three statements about the meaning of grandchildren. Beneficiaries of inheritance by substitution, Rather, the question went beyond the practical aspect, as the judicial decisions handed down by the Supreme Court differed in this context. There are also comparative Arab laws whose positions on the issue vary, between narrow and broad. The issue of disagreement does not relate to the meaning of descendants who are entitled to a compulsory will exclusively in Algerian law and justice, but the same is true of comparative Arab law, whose positions on the issue vary between narrow and broad.
Eligible for inheritance by substitution in the Algerian family law In light of Supreme Court decisions A comparative study with Arab legislation
مقال
Keywords: التنزيل؛ الوصية الواجبة؛ الأحفاد؛ قانون الأسرة؛ المحكمة العليا؛ التشريعات العربية; inheritance by substitution; Mandatory will; My grandchildren; Family law; Supreme Court; Arab legislation.